Novel investigational treatments for ventilator-associated pneumonia and critically ill patients in the intensive care unit. (1st February 2022) - Cusack, Rachael; Garduno, Alexis; Elkholy, Khalid; Martín-Loeches, Ignacio
ABSTRACT: Introduction: Ventilator-associated pneumonia (VAP) is common; its prevalence has been highlighted by the Covid-19 pandemic. Even young patients can suffer severe nosocomial infection and prolonged mechanical ventilation. Multidrug-resistant bacteria can spread alarmingly fast around the globe and new antimicrobials are struggling to keep pace; hence physicians must stay abreast of new developments in the treatment of nosocomial pneumonia and VAP. Areas Covered: This narrative review examines novel antimicrobial investigational drugs and their implementation in the ICU setting for VAP. This paper highlights novel approaches such as monoclonal antibody treatments for P. aeruginosa and S. aureus and phage antibiotic synthesis. This paper also examines mechanisms of resistance in Gram-negative bacteria, virulence factors, and inhaled antibiotics and questions what may be on the horizon in terms of emerging treatment strategies. Expert opinion: The postantibiotic era is rapidly approaching, and the need for personalized medicine, point-of-care microbial sensitivity testing, and development of biomarkers for severe infections is clear. Results from emerging and new antibiotics are encouraging, but infection control measures and de-escalation protocols must be employed to prolong their usefulness in critical illness.